A novel method for discrimination between innocent and pathological heart murmurs. Issue 7 (July 2015) - Gharehbaghi, Arash; Borga, Magnus; Sjöberg, Birgitta Janerot; Ask, Per
Highlights A robust method for discrimination between innocent and pathological murmur is presented. The method is based on statistical classification techniques. The proposed method gives the flexibility to the classifier to be trained for a demanding medical purpose, where very similar patterns are supposed to be distinguished, i.e. mild aortic stenosis and innocent murmur. The study presents a statistical validation method to evaluate the performance of the methods which is another unique feature of the presented study within this context. Results showed an improved classification and also the potential for further improvements in favor of the proposed method.